Coupled analysis for the effect of wave height on FPSO motions - Rini, N.; Kurian, V.; Liew, M.; Whyte, Andrew (2016)
© 2016 Taylor & Francis Group, London.Fully coupled time domain analysis is performed to study the effect of wave height on FPSO motions. The turret-moored FPSO used in the OTRC experimental studies were made use of to investigate the FPSO motion patterns. The study was conducted by varying the significant wave height for a particular peak period. The peak period ranges from 5-25 seconds, where the wave frequency response is significant. The results show significant variation in the horizontal and vertical motions of the FPSO, which are discussed in this paper. The results can be employed to ensure the safety and operability of the FPSO by predicting the FPSO motions where the sea state varies considerably.